BIOTECHNOLOGY AND HEALTH: ETHICAL CHALLENGES FOR INDIA - Vaz, Mario (Asian Horizons, 2013)
There is no universally accepted definition for the term Biotechnology. In this paper, I will refer to it in a fairly broad way as outlined by the UN Convention on Biological Diversity, which referred to the term as “any technological application that uses biological systems, living organisms, or derivatives thereof, to make or modify products or processes for specific use.”1 An alternative definition, also broad, which lends itself to more easy interpretation is “the processes and products (usually of industrial scale) offering the potential to alter and, to a degree, to control the phenomena of life—in plants, in (non-human) animals, and, increasingly, in human beings.”2 The second definition goes on to explain some terms more explicitly by giving examples of the processes (e.g. recombining genes) and products (e.g. new drugs or vaccines).